A Genealogy of Bamboo Diplomacy The Politics of Thai Détente with Russia and China - Poonkham, Jittipat (ANU Press, 2022)
In 1975, M.R. Kurkrit Pramoj met Mao Zedong, marking the eventual establishment of diplomatic relations and a discursive rupture with the previous narrative of Communist powers as an existential threat. This book critically interrogates the birth of bamboo (bending with the wind) diplomacy and the politics of Thai détente with Russia and China in the long 1970s (1968-80). By 1968, Thailand was encountering discursive anxiety amid the prospect of American retrenchment from the Indo-Pacific region. As such, Thailand developed a new discourse of détente to make sense of the rapidly changing world politics and replace the hegemonic discourse of anticommunism. By doing so, it created a political struggle between the old and new discourses. Jittipat Poonkham also argues that bamboo diplomacy - previously seen as a classic and continual 'tradition' of Thai-style diplomacy - had its origins in Thai détente and has become the metanarrative of Thai diplomacy since then. Based on a genealogical approach and multi‑archival research, this book examines three key episodes of Thai détente: Thanat Khoman (1968-71), M.R. Kukrit Pramoj (1975-76), and General Kriangsak Chomanan (1977-80). This transformation was represented in numerous diplomatic/discursive practices, such as ping‑pong diplomacy, petro‑diplomacy, trade and cultural diplomacy, and normal visits.